Viking law and order places and rituals of assembly in the medieval North - Sanmark, Alexandra 1970- (Edinburgh University Press, 2017)
The Vikings are well-known for their violent raids and pillage, but they also had a well-organised system for political decision-making, legal cases and conflict resolution. These activities took place at outdoor assembly sites, such as Thingvellir in Iceland, which were carefully selected for their characteristics and then maintained and rebuilt over time. Whilst not neglecting the violent elements of the Norse people, this book demonstrates that law and assembly formed an integral part of Norse life and identity, to the extent that the assembly institution was brought to all Norse settlements
Keywords: Geschichte; Politik; Wikinger; Ritual; Politisches System; Rechtssystem; Skandinavien; Atlantischer Ozean -- Nord; Schottland; Vikings / Politics and government; Political customs and rites / Scandinavia / History / To 1500; Civilization, Viking